A PROSPECTIVE STUDY OF PATTERN OF LIGATURE MARK IN CASES OF DEATH DUE TO COMPRESSION OF NECK BROUGHT TO MORTUARY IN CIVIL HOSPITAL AHMEDABAD (Journal of Forensic Medicine & Toxicology, 2016)
The ligature mark is one of the most vibrant evidences, which is very helpful in establishing the actualities in cases of death due to compression of neck by ligature. The characteristic finding, the ligature mark, found around the neck in both hanging and strangulation creates an element of doubt in many cases. It is important to study the pattern of the ligature mark to derive a conclusion in such cases. A prospective study was therefore carried out in the Department of Forensic Medicine, B. J. Medical College, Civil Hospital, Ahmedabad from January 2014 to December 2014. A total of 4137 autopsies were conducted in the year 2014 and out of these cases, 200 cases of death due to neck compression were selected for this prospective study; 194 cases (97%) were of hanging and 6 cases (3%) were of ligature strangulation. Ligature mark was oblique in direction in most cases of hanging. Complete ligature mark was seen in most cases of ligature strangulation. Ligature mark was above the level of thyroid cartilage in maximum number of cases of hanging while it was on the level of thyroid cartilage in all the cases of ligature strangulation.
Keywords: Ligature mark; Hanging; Strangulation.